Optimal Solution of Fuzzy Transshipment Problem Using Generalized Hexagonal Fuzzy Numbers - P. Ghadle, Kirtiwant; M. Ingle, Sanjivani; A. Hamoud, Ahmed (International Journal of Engineering and Technology, 2018)
In the present paper, the generalized hexagonal fuzzy number has been newly introduced to deal fuzzy transshipment problem. We solved balance and unbalance fuzzy transshipment problem by various methods. Various methods are compared to find the best solution. The objective of our paper is to find the best method for solving transshipment problem. This procedure is illustrated with numerical examples.Â Â